2022
DOI: 10.3390/ijerph191710682
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Habits and Workplace Health Promotion among University Students in Southern Italy: A Cross-Sectional Pilot Investigation

Abstract: The study aimed to investigate the tobacco smoking prevalence, habits and awareness among a cohort of healthcare students from a university hospital in southern Italy and the associations with socio-demographic determinants. A secondary outcome was to estimate the educational needs to receive information on smoking-related risk factors. Five hundred and forty-nine students completed a self-administered questionnaire (180 male and 369 female, average age 25 yo, ±5.9 SD), enrolled from October 2018 to November 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…Differences among faculties have been reported very seldom: differently from our study, Šljivo et al reported a lower prevalence of smokers in the Social Faculty (17%) than in the Technical (23.4%) and Medicine faculty (60%) in Bosnia Herzegovina [27], while Bro żek et al reported no differences between medical and non-medical students (12%) in Eastern European countries [29]. As regards the Medicine faculty, the percentage of smokers here found was much lower than in previous studies conducted in Italy among medical students, where the percentage of smokers in the 25-45% range had been reported [19][20][21][22][23]34,35].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Differences among faculties have been reported very seldom: differently from our study, Šljivo et al reported a lower prevalence of smokers in the Social Faculty (17%) than in the Technical (23.4%) and Medicine faculty (60%) in Bosnia Herzegovina [27], while Bro żek et al reported no differences between medical and non-medical students (12%) in Eastern European countries [29]. As regards the Medicine faculty, the percentage of smokers here found was much lower than in previous studies conducted in Italy among medical students, where the percentage of smokers in the 25-45% range had been reported [19][20][21][22][23]34,35].…”
Section: Discussioncontrasting
confidence: 56%
“…To the best of our knowledge, this is the first study in Italy involving the entire student population of a university and investigating several aspects related to smoking. Previous studies in Italy had been limited to single university courses, and almost exclusively in Medicine and Health professions [19][20][21][22][23]. Even if the response rate was quite moderate (11%), the study participants were broadly representative of the student population for sex, age, and faculty of enrollment (Table 1).…”
Section: Discussionmentioning
confidence: 99%